TEST OF TWO VARIETIES OF JASMINE (Jasminum sambac) AND FRUCTOSE CONCENTRATION IN Nagata and Takebe MEDIA ON SECONDARY METABOLITES CONTENT IN VITRO - Widya, Surya Ari; Bafiqi, Medita Johana Pakula; Mahdani, Hakkul Bahiz (Universitas Veteran Bangun Nusantara, 2025)
Jasmine (Jasminum sambac) is one of the ornamental plants that are widely cultivated in Indonesia and is known to have economic value and benefits in various sectors, such as the perfume, pharmaceutical, and health industries. The purpose of this study was to determine the right efficiency in the concentration of fructose addition to the callus of two varieties of Jasmine on the content of secondary metabolites. The method used was a factorial Completely Randomized Design (CRD), repeated 4 times and each replication contained 5 samples. The treatments were as follows: Factor 1 Variety: V1: Var. Jasminum officinale, V2: Var. Jasminum Grand Duke of Tuscany while in Factor 2 using the addition of Fructose concentration K1: 10 g, K2: 20g, K3: 30g. The results of the quantity and quality of callus showed the best growth in the treatment of jasmine variety Jasminum officinale with the addition of a fructose concentration of 20 g, while the highest secondary metabolite content was in the treatment of jasmine variety Jasminum officinale with the addition of a fructose concentration of 30 g.